STUDY ON EFFICACY OF COMBINATION OF HERBAL OIL (NEEM & KARANJ OIL) AND DELTAMETHRINAGAINST HYALOMMA.ANATOLICUM. ANATOLICUM INFESTATION IN CROSSBRED COWS - Dadhich, SR; Deshwal, AK; Tailor, RS; Panchlaniya, AK (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was carried out to compare efficacy of combination of herbal oil and acaricide delta methrin in crossbed cows. Application of the neem and Karanja oil was found to be economically beneficial as compared to the farmers practice (in which deltamethrin 2ml/lit. was used).